The effect of service quality on revisit intention: The mediating role of destination image - Masimba Elvis Manyangara; Charles Makanyeza; Zororo Muranda (Cogent Business & Management, 2023)
The study investigates the effect of service quality on revisit intention and the mediating role of destination image. Data were gathered from tourists who visited ZimParks tourist destinations (n = 400) using structured questionnaires. The study adopted a cross-sectional survey. Findings show that service quality positively influences revisit intention. Service quality is found to have a positive impact on destination image. Findings also reveal that destination image significantly impacts revisit intention. Destination image was found to mediate the effect of service quality on revisit intention. The findings contribute to the existing body of tourism and marketing literature. Destination Management Companies (DMCs) are advised to consider service quality and destination image when developing strategies to improve tourist revisit intention.
Keywords: 650; destination image; revisit intention; service quality; Zimbabwe Parks and Wildlife Management Authority